VIDEO ANIMASI: MEDIA BIMBINGAN KARIR BAGI GEN Z - Aini, Jannatun; Hartini, Hartini; Rizal, Syamsul (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2024)
This research aims to examine in the literature what the problems and needs of Generation Z are in career selection and development. This research uses literature methodology. Data is collected from literature, such as books, journals and notes. This article discusses the meaning, theory, previous research findings, and hypotheses regarding the relationship between the use of guidance and counseling media and the desire to use these services. Content analysis is the analysis method used. The results of the study show that there are various problems of Gen Z in terms of career such as social media where Gen Z cannot utilize social media properly and use social media not for learning, career planning influenced by authoritarian parenting, Gen Z's career expectations are too high while work experience and skills are minimal, as well as the influence of global competition that requires Gen Z to compete using qualified skills. The many problems make Gen Z need various things related to their careers, namely career development, salary, work life balance, flexibility, and work location. the use of information technology, especially with the existence of animated video media, in guidance and counseling services in an effort to meet needs and overcome problems in terms of career guidance, counselors can use animated videos that are made as attractive as possible for Generation Z by using animated videos that contain various materials that can improve the understanding, information, insight and knowledge of Generation Z regarding the careers they will pursue in the future